INCREASING COMMUNITY EDUCATION ON COASTAL ENVIRONMENTAL SUSTAINABILITY THROUGH THE BEACH CLEAN MOVEMENT IN MAMALA VILLAGE, REGENCY. MALTENG - Wally, Pramita; Kaliky, Nurainy (Batara Wisnu : Indonesian Journal of Community Services, 2023)
The purpose of this community service activity is to increase public awareness in order to protect the coastal area of ??Mamala Country so that it is free from garbage. The method used in this service is the method of observation and participation with three stages of activity for participants, namely before the activity, carrying out the activity and after the activity. This service activity was carried out at Mamala State Beach, Leihitu District, Central Maluku Regency, attended by 22 people consisting of lecturers, local communities and tourists. This beach clean movement activity can be carried out smoothly in accordance with the planned activities. This activity can develop the mindset of the community and increase their concern in preventing environmental pollution which in turn can make the beach clean, beautiful and comfortable and can increase the visiting power of tourists to the beach